Undermining Democracy: The Rise of Congressional Exploitation in America and its Impact on International Image - Qaiser, Lubna; Ijaz, Ayesha; Batool, Imman (Pakistan Languages and Humanities Review, 2024)
The paper explores the complexity and problems faced by American democracy, with specific focuses on congressional dysfunction, interest group politics, and foreign policy as aspects of the national image that foreigners perceive. Productivity hit an all-time low in the 118th Congress, this situation has seen advocacy groups, like the AIPAC, or American Israel Public Affairs Committee, and have greater leverage on the U.S. foreign policy on matters about Israel, due to greater spending on politics after the attack by Hamas in October 2023. It concludes that erosion of democratic integrity within the United States not only weakens its domestic governance but also its international credibility and influence, especially on matters like human rights and democratic advocacy in the world.